The revocation as a constitutional mechanism of political participation in the face of the loss of confidence of the Peruvian parliament. - Meza Vásquez, Lourdes Pamela (2013)
Objective: Pose the revocation of Congress, in order that the parliamentary mandate can be shortened and that its management can be subject to in a more frequent monitoring, so that we do not have to put up with a bad representative the five year term of government. Method: Use of the deductive method, being framed in the type of applied research and substantiated explanatory level, having used techniques and data collection instruments, specifically the analysis of documentary sources and the survey, the same as was done in the city of Tacna, and which complied with my objectives and my hypothesis testing. Results: We obtained 90% of adoption to the introduction of the revocation of the Peruvian Congress and 10% do not approve. Conclusions:That the loss of confidence of our Peruvian parliament, the revocation be necessary to introduce as a constitutional means of political participation in order to strengthen democracy, which is what we characterizes every rule of law.